Clustering as a mechanism of enhanced adsorption - Vakarin, E.V.; Holovko, M.F. (Condensed Matter Physics, 2003)
The role of adsorbate clustering in increasing the adsorption on crystalline surfaces is analyzed in terms of the lattice gas model combined with the results of the associative theory. The effect of the cluster size and architecture in equilibrium and transport properties is studied. Some conjectures related to HCl-ice interfaces are drawn.